Information domain approach to the investigation of cardio-vascular, cardio-pulmonary and vasculo-pulmonary causal couplings - Luca eFaes; Giandomenico eNollo; Alberto ePorta (Frontiers in Physiology, 2011)
The physiological mechanisms related to cardio-vascular (CV), cardio-pulmonary (CP) and vasculo-pulmonary (VP) regulation may be probed through multivariate time series analysis tools. This study applied an information domain approach for the evaluation of nonlinear causality to the beat-to-beat variability series of heart period (t), systolic arterial pressure (s) and respiration (r) measured during tilt testing and paced breathing protocols. The approach quantifies the causal coupling from the series i to the series j (Cij) as the amount of information flowing from i to j. A measure of directionality is also obtained as the difference between two reciprocal causal couplings (Di,j=Cij-Cji). The method was applied on t, s, and r series measured in 15 young healthy subjects in the supine (su) and upright (up) positions, and in further 15 subjects during spontaneous (sp) and paced (pa) breathing. In the control condition (su, sp), a noticeable causal coupling (median over subjects > 0) was observed for Crs, Crt, Cst, and Cts; statistically significant directionality was set only from r to t (Dr,t>0). During head-up tilt (up, sp), Crs was preserved, Crt decreased to zero median, and Cst and Cts increased significantly; directionality vanished between r and t (Dr,t=0) and raised from s to t (Ds,t>0). During paced breathing (su, pa), Crs increased significantly, Crt and Cts were preserved, and Cst decreased to zero median; directionality was preserved from r to t, and raised from r to s (Dr,t>0, Dr,s>0). These results suggest that the approach evidences modifications of CV, CP and VP mechanisms consequent to altered physiological conditions, such as the baroreflex engagement and the dampening of respiratory sinus arrhythmia induced by tilt, or the respiratory driving on arterial pressure induced by paced breathing. Thus, it can be suggested as a tool for the noninvasive monitoring of cardiovascular and cardiorespiratory control systems in normal and impaired conditions.